Mantle Potential Temperature Estimates and Primary Melt Compositions of the Low-Ti Emeishan Flood Basalt - Shellnutt, J. G.; Pham, Thuy T. (Frontiers in Earth Science, 2018)
The Late Permian Emeishan large igneous province (ELIP) is considered to be one of the best examples of a mantle plume derived large igneous province. One of the primary observations that favour a mantle plume regime is the presence of ultramafic volcanic rocks. The picrites suggest primary mantle melts erupted and that mantle potential temperatures (TP) of the ELIP were > 200oC above ambient mantle conditions. However, they may represent a mixture of liquid and cumulus olivine and pyroxene rather than primary liquids. Consequently, temperature estimates based on the picrite compositions may not be accurate. Here we calculate mantle potential temperature (TP) estimates and primary liquids compositions using PRIMELT3 for the low-Ti (Ti/Y < 500) Emeishan basalt as they represent definite liquid compositions. The calculated TP yield a range from 1400oC to 1550oC, which is consistent with variability across a mantle plume axis. The primary melt compositions of the basalts are mostly picritic. The results of this study indicate that the Emeishan basalt was produced by a high temperature regime and that a few of the ultramafic volcanic rocks may be indicative of primary liquids.